Factors influencing clean and healthy lifestyle behavior (PHBS) on the educational personnel of Cenderawasih University in 2025 - Steny Persilla Geetruida Korwa; Arius Togodly; Muhammad Akbar Nurdin; Novita Medyati; Septevanus Rantetoding; Wahyuti Wahyuti (Journal of Multidisciplinary Academic and Practice Studies, 2025)
Purpose: This study aims to analyze the effects of knowledge, attitudes, actions, facilities, leadership support, and work environment on Clean and Healthy Living Behavior (PHBS) among education personnel at Cenderawasih University. Research methodology: The location of the study was at Cenderawasih University, in all Education Personnel in each section at Cenderawasih University totaling 243. The sample in this study used the Lemeshow formula. Stratified random sampling technique of employees totaling 165 employees. Analysis Methodusing Univariate analysis, Bivariate analysis, and Multivariate analysis. Results: The results show that attitudes, actions, facilities, and leadership support significantly influence PHBS at Cenderawasih University, while knowledge and work environment do not. Conclusions: In general, simultaneously; knowledge, attitudes, actions, infrastructure, leadership support, and work environment influence the implementation of clean and healthy living behavior at Cenderawasih University Limitations: This study focuses only on education personnel at Cenderawasih University, limiting generalizability to other institutions. Its cross-sectional design cannot assess causality, and concentrating on six variables may exclude other determinants. Self-reported data also pose response bias. Contribution: This study enriches PHBS literature by offering empirical evidence from Eastern Indonesia. It shows attitudes, actions, infrastructure, and leadership support as key factors, while knowledge and work environment are less influential. Practically, it guides universities to strengthen leadership, improve facilities, and design interventions that promote sustainable PHBS practices.